Higher-Order Risk Preferences – Consequences for Test and Treatment Thresholds and Optimal Cutoffs - Stefan Felder; Thomas Mayrhofer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Higher-order risk attitudes include risk aversion, prudence, and temperance. This paper analyzes the eff ects of such preferences on medical test and treatment decisions, represented either by test and treatment thresholds or - if the test characteristics are endogenous - by the optimal cutoff value for testing. For a risk-averse decision maker, treatment is a risk reducing strategy since it prevents the low health outcome that forgoing treatment yields in the sick state. As compared to risk neutrality, risk aversion thus reduces both the test and the treatment threshold and decreases the optimal cutoff . Prudence is relevant if a comorbidity risk applies in the sick state. It leads to even lower thresholds and a lower optimal cutoff . Finally, temperance plays a role if the comorbidity risk is left-skewed. It lowers the thresholds and the optimal cutoff even further. These findings suggest that diagnostics in low prevalence settings (e.g. screening) are considered more beneficial when higher-order risk preferences are taken into account. – – Risikoverhalten höherer Ordnung umfasst Risikoscheue, das Vorsichtsmotiv und Temperenz. Letzeres bedeutet eine allgemeine Zurückhaltung, sich Risiken auszusetzten. Wir beschäftigen uns im Aufsatz mit den Wirkungen solcher Risikopräferenzen auf diagnostische und therapeutische Entscheidungen in der Medizin, insbesondere auf die Test- und Behandlungsschwellen und, im Falle von endogenen Tests, auf den optimalen Trennpunkt. Für risikoscheue Entscheider bedeutet eine Behandlung insofern eine risikomindernde Strategie, als sie den schlechten Gesundheitszustand vermeidet, der eintritt, falls der tatsächlich erkrankte Patient nicht behandelt wird. Im Vergleich zu Risikoneutralität senkt daher das Vorliegen von Risikoscheue die Test- und Behandlungsschwellen und auch den Trennpunkt. Das Vorsichtsmotiv ist dann von Bedeutung, wenn Komorbidität im Krankheitsfall auftritt. Es führt zu einer weiteren Reduktion der Schwellen und des Trennpunkts. Temperenz kommt ins Spiel, wenn das Komorbiditätsrisiko linksschief verteilt ist. Sie reduziert die Schwellen und den Trennpunkt noch weiter. Diese Ergebnisse legen es nahe, der Diagnostik im niedrigen Prävalenzbereich - dazu gehören insbesondere Vorsorgeprogramme beim Brustkrebs und beim Prostatakrebs - eine höhere Bedeutung zuzumessen.
Keywords: D81; I10; 330; Medical decision making; diagnostic risk; test and treatment thresholds; optimal cutoff; risk aversion; prudence; Medical decision making; diagnostic risk; test and treatment thresholds; optimal cutoff; risk aversion; prudence